Balancing Integration and Role Delineation in Public Addiction Services: Insights from Northern Italy - Menara, Barbara (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study explored the complex dynamics within multidisciplinary organizations involved in addiction treatment services by investigating how professional roles, operational tasks, and systemic challenges interact and affect overall performance and service outcomes. The research was conducted within public services for addictions in Northern Italy, utilizing an ethnographic approach that included participant observation and semi-structured interviews with professionals from various disciplines. An analysis of the organizational system revealed inconsistencies between the intended goals and actual strategies, with a homogeneous approach aimed at increasing the similarities among professional categories. Upon closer examination, this homogeneous approach revealed several challenges including an unclear delineation of professional groups and overlapping responsibilities. Consequently, an excess of integrative work was observed, potentially compromising the system functionality and efficiency. While integration is important, our findings suggest the need to balance integration with other systemic functions and clearly define roles in multidisciplinary settings. By employing an ethnographic approach to public services for addictions, this study provides a novel perspective on organizational structure and its impact on service delivery. The application of Parson’s four-function paradigm to understanding system functionality also offers fresh insights into the complexities of these organizations.